Sororin actively maintains sister chromatid cohesion. (22nd February 2016) - Ladurner, Rene; Kreidl, Emanuel; Ivanov, Miroslav P; Ekker, Heinz; Idarraga‐Amado, Maria Helena; Busslinger, Georg A; Wutz, Gordana; Cisneros, David A; Peters, Jan‐Michael
Abstract: Cohesion between sister chromatids is established during DNA replication but needs to be maintained to enable proper chromosome–spindle attachments in mitosis or meiosis. Cohesion is mediated by cohesin, but also depends on cohesin acetylation and sororin. Sororin contributes to cohesion by stabilizing cohesin on DNA. Sororin achieves this by inhibiting WAPL, which otherwise releases cohesin from DNA and destroys cohesion. Here we describe mouse models which enable the controlled depletion of sororin by gene deletion or auxin‐induced degradation. We show that sororin is essential for embryonic development, cohesion maintenance, and proper chromosome segregation. We further show that the acetyltransferases ESCO1 and ESCO2 are essential for stabilizing cohesin on chromatin, that their only function in this process is to acetylate cohesin's SMC3 subunit, and that DNA replication is also required for stable cohesin–chromatin interactions. Unexpectedly, we find that sororin interacts dynamically with the cohesin complexes it stabilizes. This implies that sororin recruitment to cohesin does not depend on the DNA replication machinery or process itself, but on a property that cohesin acquires during cohesion establishment. Synopsis: Sororin is required for sister chromatid cohesion by stabilizing vertebrate cohesin on chromatin after DNA replication. The interaction of sororin with cohesin only occurs on replicated chromatin and is short‐lived. Sororin is recruited to cohesin directly at sites of DNA replication Sororin is continuously required for sister chromatid cohesion also after DNA replication Sororin protein levels correlate with the number of cohesin molecules that are stabilized on chromatin These cohesin–chromatin interactions persist for many hours, while the sororin–chromatin interaction is highly dynamic Abstract : Sororin is required for sister chromatid cohesion by stabilizing vertebrate cohesin on chromatin after DNA replication. The interaction of sororin with cohesin only occurs on replicated chromatin and is short‐lived.